Schools and Communities : Working together to transform children''s lives. - West-Burnham, John (Bloomsbury Publishing, 2007)
This book is rooted in the principle that every child and young person has a fundamental entitlement to equal educational opportunities. Human relationships are fundamental to educational and social development and increasing importance is being attached to cooperation and collaboration between schools and the community, and between the agencies that provide services for children and young people.